Wanprestasi Dalam Perjanjian Asuransi (Studi Putusan PN Jakarta Selatan Nomor 482/PDT.G/2020/PN JKT.SEL) - Moody Rizky Syailendra; King William; Gavriele Liberty (Jurnal Ilmiah Wahana Pendidikan, 2023)
Insurance agreements in their implementation often lead to legal problems, where the insurance party is often negligent in their responsibilities which results in default. This often becomes a problem that ends up in court and the judge acts as a mediator. This study aims to add insight to the readers, as well as provide a clear sequence and flow so that it makes it easier for the reader to understand. This study uses a normative juridical method and discusses cases related to acts of default, which resulted in the Defendant being declared defeated and having to be punished with a portion of the lawsuit filed by the Plaintiff. From this case it can be concluded that the agreement is a bond that must be carried out by both bound parties, and the responsibilities of both parties must be fulfilled and if not carried out, then there is a penalty that must be met by the originating party. The author believes that all considerations and judges' decisions are fair to restore the rights of both parties